Comprehending Assimilation Pattern by Tracing Its Phonological Process: Input, Environment, and Process - Sadiq, Nizamuddin (English Education Department, Universitas Islam Indonesia, 2009)
Native speakers, English mother tongue, speak naturally. Although they do not think the way how they are pronouncing words, they seem to simplify their speeches-Therefore, it is often difficult to understand what is spoken by them because it is heard like babbling. One of the simplifications of speeches is assimilation. Assimilation is one of phonological processes. Comprehending its phonological process means understanding its input, environment, and process. Therefore, all phenomena of pronunciation particularly assimilation are collected and then they are classified and described one by one based on its input, environment and process. The result of the research is that to anticipate the preceding word, the first is anticipating the preceding: a) when alveolar is preceded by bilabial, alveolar will anticipate the bilabial by changing alveolar into bilabial, b) when alveolar is preceded by velar, alveolar will anticipate the velar by changing alveolar into velar, c) when alveolar is preceded by palato alveolar, alveolar will anticipate by changing into palato alveolar.